Blockchain in agri-food chain : shaping an integrated food ecosystem - Davidsson, Madeleine (SLU/Dept. of Urban and Rural Development, 2019)
Agriculture is on the brink of entering a data-driven economy that will impact growth and business relations. The information- and communication revolution in the agri-food chain aspires to collect data at a low cost. Applying information- and communication technologies to the agri-food chain is believed to help optimise resources and therefore contribute to a smaller environmental footprint. At present, however, there are barriers and many issues that need to be resolved; For example, it is not an easy task to aggregate and interpret large amounts of detailed data to be used in decision support tools for farmers and primary producers. There are also transparency issues due to numerous intermediaries and a need for strengthening the link between different chain actors and levels in the agri-food chain. The agricultural has never before undergone such a digital transformation.